Administrasi Guru dan Kegiatan Belajar Mengajar - Fatimah, Meti; Dewi, Rachma Rusdiana; Al Mustofa, Ahmad (Lembaga Yasin AlSys, 2026)
Teacher administration is a key component of learning management that plays a strategic role in supporting the effectiveness of teaching and learning activities, particularly in the context of Islamic education that is oriented toward the formation of noble character. This article aims to examine the role of teacher administration and its relevance to the implementation of teaching and learning activities as well as the integration of Islamic values in Islamic Religious Education (PAI) instruction. The study employed a qualitative approach with a library research method by reviewing books, legislation, and relevant scholarly journal articles, with data analyzed descriptively and analytically to obtain a comprehensive understanding of the concepts and practices of teacher administration in learning. The findings show that teacher administration encompasses the administration of planning, implementation, and evaluation of learning, which are interrelated and inseparable; orderly and systematic administration management helps enhance teaching readiness, teacher professionalism, the quality of the learning process, and student learning outcomes. In Islamic education, teacher administration functions not only as an instrument of academic management but also as an important means for internalizing Islamic values and forming students’ religious character through planning, implementation, and evaluation processes grounded in those values. Therefore, strengthening teacher administrative competencies needs to be carried out continuously through coaching, training, and supervision so that instruction, particularly PAI, can take place effectively, meaningfully, and with a clear orientation toward the formation of noble character.